Three-dimensional dynamic optical trapping using non-iterative computer-generated holography. (May 2023) - Sun, Fengyu; Zhu, Linwei; Wang, Wenpeng; Shi, Zhiyong; Liu, Yanqi; Xu, Yi; Shi, Qiang; Leng, Yuxin; Li, Ruxin
Highlights: The focal spot with accurate position can be straightforwardly realized. Apply two non-iterative methods to achieve multifocal spots with accurate position. The complex amplitude coding method produced multifocal spots with higher uniformity and stability than the fan-shaped subzone phase method. Three-dimensional particle manipulation dynamic optical trapping experiment. Abstract: Holographic optical trapping enables three-dimensional (3D) particle manipulation based on a traditional iterative algorithm. However, this type of particle manipulation is typically unstable. It is challenging to realize continuous dynamic 3D optical trapping because a unique solution of uniformity cannot be obtained over several time-consuming iterations. In this study, 3D multifocal spots with high uniformity were generated via non-iterative algorithms (using a complex amplitude coding method and fan-shaped subzone phase method) to realize stable dynamic optical trapping for 3D particle manipulation. The corresponding experimental results pave the way for potential applications of colloid transport and the micro-assembly of objects in the micro-operation field.